2019
DOI: 10.1017/s0714980818000685
|View full text |Cite
|
Sign up to set email alerts
|

Retirement Expectations of Older Workers with Arthritis and Diabetes Compared with Those of Workers with No Chronic Diseases

Abstract: RÉSUMÉLes plans de retraite des adultes atteints de maladies chroniques sont peu connus. Dans le cadre de cette étude, des travailleurs canadiens âgés de 50 à 67 ans provenant d’un regroupement national de 80 000 personnes (arthrite, n = 631 ; diabète, n = 286 ; arthrite et diabète, n = 111 ; aucune maladie chronique invalidante, n = 538) ont participé à une enquête transversale sur ce sujet. Les questions posées aux participants traitaient de l’âge prévu pour leur départ à la retraite, de leurs plans de trava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…For people with MSK conditions, maintaining capacity to work is known to contribute physical benefits, including sustained joint strength, and psychological benefits, such as social engagement and brain activity [88]. In contrast, some workers across the age spectrum with MSK conditions may struggle with the demands of work, and consider a thought-out plan for early retirement as optimal for physical and mental health outcomes [89]. The opposite can also be true: some workers push to maintain their work status to the detriment of their physical capacity, whereas others retire early without proper planning or intervention to attempt to remain at work.…”
Section: Facilitators and Challenges In Enabling Worker Retentionmentioning
confidence: 99%
“…For people with MSK conditions, maintaining capacity to work is known to contribute physical benefits, including sustained joint strength, and psychological benefits, such as social engagement and brain activity [88]. In contrast, some workers across the age spectrum with MSK conditions may struggle with the demands of work, and consider a thought-out plan for early retirement as optimal for physical and mental health outcomes [89]. The opposite can also be true: some workers push to maintain their work status to the detriment of their physical capacity, whereas others retire early without proper planning or intervention to attempt to remain at work.…”
Section: Facilitators and Challenges In Enabling Worker Retentionmentioning
confidence: 99%
“…Findings did not support our second hypothesis, which posited that younger workers with a disability would be more likely to work precariously when compared to older adults with a disability. Advances in treatment and self-management have meant that people living with disabilities are living longer and working later into their lives [45]. Past studies of older workers indicate that a disability may disrupt one's ability to perform workplace acts and tasks, and to keep up with the schedule and pace of work [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in treatment and self-management have meant that people living with disabilities are living longer and working later into their lives [45]. Past studies of older workers indicate that a disability may disrupt one's ability to perform workplace acts and tasks, and to keep up with the schedule and pace of work [45,46]. Also, research on people not living with a disability also highlight less occupational mobility (i.e., perceived ability to change work) among older workers when compared to younger workers [29].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that 8.5%-23.8% of workers were neutral about delaying retirement. Researchers suggested that "do not know when will retire" was also meaningful (Gignac et al, 2019). However, the neutral attitude or "do not know" about retirement has often been neglected in previous empirical studies.…”
Section: T a B L E 2 Multinomial Logistic Regression On Delayed Retir...mentioning
confidence: 99%
“…Job satisfaction reflects how workers feel about their work. Workers who are dissatisfied with their work were more likely to retire early (Gignac et al, 2019; Kubicek et al, 2010).…”
Section: Introductionmentioning
confidence: 99%